Pelatihan dan Implementasi Perencanaan Karir Siswa Pasca Lulus Sekolah Pada SMK - Setiadi, Teguh; Fajri, Laksamana Rajendra Haidar Azani; Ilhami, Susanti Dwi (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
Vocational high school education is an important path to foster skilled professionals with skills in accordance with their fields and is increasingly attracting attention in the world of work. Vocational education emphasizes the development of practical skills and vocational competencies of students. This equips them with the ability to adapt quickly to market demands and contribute to social and economic development, one of which is at SMKS Harapan Mulya Kendal. Along with the advancement of globalization and technology, career planning has evolved beyond just career selection; career planning has become a comprehensive process that requires consideration of various factors such as personal interests, values, skills, and job market requirements. This community service aims to implement the application of smart career applications for vocational high school students, with the aim of helping them better overcome challenges in the workplace and realize their respective career goals before graduating from school. The implementation of community service activities focuses on solving problems, namely student human resources and counseling guidance in order to improve the quality of student careers, and understanding the career potential of vocational high school students.